혈액투석 환자에서 항인지질 항체와 동정맥루 폐쇄의 상관관계에 대한 연구 - 강덕희; Duk Hee Kang; 유승기; Seung Ki Ryu; 김성남; Sung Nam Kim; 최규복; 윤견일; Kyun Il Yoon; 이윤하; Yoon Ha Lee (The Korean journal of medicine, 1997)
Objectives: Anticardiolipin antibody (ACA) and lupus anticoagulant (LA) are acquired antiphospholipid antibodies (APAs), which are regarded as important risk factors far vascular thrombosis and recurrent fetal loss. Although the clinical relevance of APAs in dialysis patients is uncertain, recent studies have suggested that APAs are involved in bioincompatibility and thrombogenic complications in hemadialysis (HD) patients. Method : We performed a cross sectional study of ACA and LA in 50 stable HD patients and their 68 vascular accesses (52 native arteriovenous fistulae and 16 synthetic arterovenous grafts), with the analysis of factors associated with the presence of APAs and the retrospective evaluation of vascular access occlusion (VAO). LA was assessed by platelet neutralization method whereas IgG-ACA was measured by a solid phase ELISA. Values higher than 23GPLU/ml (IgG phospholipid units) were considered to be positive for IgG-ACA and positive values for LA was more than 8 seconds in prolongation of the clotting time with human platelet lysate. Vascular access survival was assessed by Kaplan- Meier method, Results: The mean age of the subject (M:F 21:29) was 46 years and the mean duration of hemodialysis was 49 months. The frequency of VAO in entire subjects was 0.45±0.98 episodes/patient year. The median value of IgG-ACA was 16.0 GPLU/ml with a distribution from 2.7 to 46.1GPLU/ ml. The median titer of I.A was 4.5 (3.1-45.6) seconds. Fourteen patients (28%) were found to have at least one episode of VAO. In spite of comparable clinical and biochemical data according to the presence of VAO, the titers of IgG-ACA (13.6±7.7 vs, 20.3±8.7GPLIJ/ml, P<0.05) and LA (4.5±2.9 vs. 11.7 ±12.6sec, P<0.05) were significantly higher in VAO group. Six out of 50 patients(12%) had an increased titer of IgG-ACA and LA was found in 11 patients(22%). No patients were positive for ACA and LA simultaneously. There was no significant difference in sex, etiology of ESRD, diabetic status, the dosage of heparin during HD or the amount of erythropoietin administered according to the presence of APAs. We could not find any significant correlation between the titer of APAs and age, duration of dialysis, blood pressure, platelet count and biochemical parameters. In the patients with positive ACA, the frequency of VAO was 1.05±0.12 episodes/patient · year, which was significantly higher than patients without ACA (0.33±0.17 episodes/ patient year, P<0.05). In the patients with the presence of LA(1.06±0.43 vs. 0.12±0.06 episodes/ patients · year, P<0.01). The median vascular access survival time in IgG-ACA positive patients (32.7 months) was significantly decreased compared to 66.8 months in IgG-ACA negative group. Conclusion: Our data suggest that the presence of APAs (ACA and/or LA) affects the event-free vascular access survival in HD patients. Therefore the evaluation of APAs status have to be included in the diagnostic strategies for the patients with recurrent VAO. Further studies are necessary to explore the pharmacologic intervention method to decrease APAs and prevent VAO in HD patients.